Koncept regionalnega prostorskega razvoja Slovenije - Gulič, Andrej (Geographica Slovenica, 2000)
The new Physical (Spatial) Plan of the Republic of slovenia will, among other, comprise also a concept of regional spatial development. in this paper,some of the main steps to, and results of, elaboration of such a concept are presented: definitions of terms development, regional development and regional spatial development; development challenges from the inner and outer environment by topics - the settlement system, transport infrastructure, landscape, economy, quality of life - and the concept of realizable responses of actors to them on four territorial levels; description of the spatial elements of the concept as well as of its concrete reflection in the spatial systems.
Keywords: regionalni razvoj; prostorski razvoj; regionalno planiranje; regije; Slovenia; Slovenija